Grupo terapêutico on-line: processo de tomada de consciência e identificação - Araújo, Micaela Brandão Póvoa de (2024)
The COVID-19 pandemic has had significant impacts on the mental health of university students, especially due to changes in teaching-learning processes. The first study outlined how an online therapeutic group strengthened bonds between participants and facilitated awareness and the process of change in the face of psychological distress during this challenging period. In the second article, I brought the experiences of students when returning to face-to-face activities and the difficulties generated by this return. The intervention research, based on the Gestalt therapy approach, analyzed the students' experiences in relation to the changes caused by COVID-19, as well as the process of group identification and its contribution to caring for these students' suffering. Data analysis was carried out using the Meaning Analysis proposed by Critelli, in which the results indicated that the online therapeutic group provided a space of acceptance and awareness of the suffering experienced in the university context, highlighting its effectiveness as a tool to promote mental health care and quality of life during the pandemic for this specific group.